Comparison of Manual and Automated Nucleic Acid Extraction Methods for HCV - RNA Assays (GAIMS Journal of Medical Sciences, 2024)
Background: Hepatitis C Virus (HCV) infection is the most leading cause of chronic hepatitis in world and it is more prone to cause cirrhosis and carcinoma of liver. Hence, early diagnosis of this virus infection may be helpful to prevent these complications. First step in diagnosis of HCV infection is Enzyme Linked Immunosorbent Assay (ELISA), but it cannot differentiate people who are chronically infected from people who had spontaneous resolution, so molecular method by HCV-RNA detection is more helpful. HCV-RNA extraction is done by two methods, manual and automated method.Material and methods: In present study, we compared amplification results of HCV-RNA which were extracted by both methods. Automated method is more sensitive than manual method as manual method is time consuming, more cumbersome and has high risk of contamination.Results: Out of 100 samples, amplification result of 16 samples were found to be positive by HCV-RNA which were extracted by automated method but negative by manual method. The data was analysed using Microsoft Excel.Conclusion: Automated method has high sensitivity and less chance of contamination.